(untitled) (REMUNOM, 2025)
The public sector is characterized by the need for managers to develop and implement management policies that promote both the recruitment and retention of committed and satisfied civil servants, enabling them to operate in complex and dynamic environments. In this regard, the present study aimed to analyze the relationships between job satisfaction and organizational commitment in the Brazilian public sector. To achieve this objective, a systematic literature review was conducted, covering the period from 2016 to 2025, seeking studies that examine the relationship between these constructs within the context of the Brazilian public sector. The results indicate that there is a mutual influence between job satisfaction and organizational commitment, and that job satisfaction may be related to different dimensions of commitment. Furthermore, higher levels of satisfaction are associated with higher levels of commitment among public servants. Job satisfaction may also act as a mediator between organizational culture and employee commitment, as well as between role overload at work and commitment.